2006
DOI: 10.1111/j.1445-2197.2006.03896.x
|View full text |Cite
|
Sign up to set email alerts
|

Are Biochemical Values Predictive of Adenoma’s Weight in Primary Hyperparathyroidism?

Abstract: Preoperative PTH level cannot be used as a definite guide to the parathyroid adenoma's weight. Large parathyroid adenomas seem to secrete less PTH per unit weight than small adenomas. Calcium and phosphate do not seem to be of much value in predicting adenoma's weight in primary hyperparathyroidism.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
25
2

Year Published

2006
2006
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(29 citation statements)
references
References 16 publications
2
25
2
Order By: Relevance
“…In the present study, although PHPT was found to be more prevalent in women (31 of 50), the female-to-male ratio (1.63) is somewhat different from that found in other large series conducted in Western [2,5,8] or Eastern countries [9,10]. However, in one series conducted in Hong Kong, the female-to-male ratio was determined to be 1.98, which is similar to our findings [11].…”
Section: Discussioncontrasting
confidence: 63%
“…In the present study, although PHPT was found to be more prevalent in women (31 of 50), the female-to-male ratio (1.63) is somewhat different from that found in other large series conducted in Western [2,5,8] or Eastern countries [9,10]. However, in one series conducted in Hong Kong, the female-to-male ratio was determined to be 1.98, which is similar to our findings [11].…”
Section: Discussioncontrasting
confidence: 63%
“…reported a series of 63 patients in whom there was a significant correlation between calcium and PTH levels and PTA weight and volume. More recent studies, which evaluated cohorts of about 70 patients, found no correlation at all …”
Section: Discussionmentioning
confidence: 93%
“…More recent studies, which evaluated cohorts of about 70 patients, found no correlation at all. 11,18 A possible explanation for the discrepancy between studies could be the differences in baseline confounding factors such as calcium intake and absorption, serum albumin, renal function and vitamin D levels. It has been reported that vitamin D deficiency may be associated with heavier parathyroid adenomas probably due to secondary hyperparathyroidism 20,21 , but this association is poorly understood 22 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Management has therefore evolved to use patient pre‐operative biochemical markers such as serum calcium and parathyroid hormone (PTH) as further guides to gauge the presence of smaller adenomas. However, this biochemical relationship remains unclear with many researchers noting direct correlations and others who refute their value in predicting adenoma weight . To add to the complexity, smaller adenomas appear to be linked with non‐localizing imaging, making pre‐operative localization increasingly more technically difficult than solitary larger adenomas …”
Section: Introductionmentioning
confidence: 99%